(untitled) (International Journal of Engineering and Computer Science, 2014)
This article explores the how the mobile devices is used for improving health care system. M-health—mobile applications for healthcare—is a young and dynamic field that could improve the well-being of people around the world. Mobile applications can lower costs and improve the quality of healthcare as well as shift behavior to strengthen prevention, all of which can improve health outcomes over the long term. Mobile technologies are increasingly growing in developing countries like India. There have been several new researches and developments in this space. Nowadays mobile is becoming an important ICT tool not only in urban regions but also in remote and rural areas. The rapid advancement in the technologies, ease of use and the falling costs of devices, make the mobile an appropriate and adaptable tool to bridge the digital divide. Mobile phone ownership in India is growing rapidly, six million new mobile subscriptions are added each month and every one will own a phone by the end of 2014. By the end of 2015, three quarters of India’s population will be covered by a mobile network. Many of these new "mobile citizens" live in poorer and more rural areas with scarce infrastructure and facilities, high illiteracy levels, low PC and internet penetration. The availability of low-cost mobile phones and the already broad coverage of GSM networks in India is a huge opportunity to provide services that would trigger development and improve people’s lives. The objective of this paper is to bring out status of mobile devices based Health care management systems in the world particularly in India.